Management of Facilities and Infrastructure Development of Athletic Sports Branch of Tulang Bawang District - Ayunita, Devi; S, Fransiskus Nurseto; Kurniawan, Candra; Wicaksono, Lungit (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Adequate training facilities and infrastructure are needed to support the athletic training process activities to make it easier for Athletes and Coaches when training, so that from the training process it is hoped that all Athletes will gain a lot of learning experience and be able to train optimally. This research aims to find out the athletic numbers that have the greatest chance of winning in Tulang Bawang district athletics based on the facilities and infrastructure that are available and whether they are PASI standard or not. The research method used is qualitative research with a descriptive approach. Data collection uses observation, interviews and documentation. The instruments used are interview and documentation instruments. The population in this study were the PASI Tulang Bawang branch administrators in Tulang Bawang Regency. Samples taken from purposive sampling, with criteria; (1) The PASI Tulang Bawang District Administrator who is in Tulang Bawang Regency, (2) is still active as the Tulang Bawang District PASI District Administrator, (3) who is often present or directly involved in the field ((coaches, athletes, referees). From the results of this research, it can be concluded that (1) the Facilities Factor is in the good category, the Infrastructure Factor is categorized as adequate, many of the facilities and infrastructure for athletic sports in Bone Bawang Regency are not yet standardized with PB PASI, there are still many facilities and infrastructure that use modified equipment in the training program , (2) Athletic numbers that can be developed in accordance with the existing Facilities and Infrastructure at PASI Tulang Bawang are javelin throw, discus throw, shot put, long jump and long distance running. In fact, the short distance running and hurdles events can actually be trained in Tulang Bawang, but training will not be optimal after looking at the existing infrastructure, and the management of the facilities and infrastructure of Pengcab PASI Tulang Bawang is not running well.